Alternanthera kanhae (Amaranthaceae), a new species from Sabarmati Estuary of India - Vanzara, Akash G.; Katara, Ilesh; Nagar, Padamnabhi S. (Phytotaxa, 2021)
A new species of Amaranthaceae, Alternanthera kanhae, is described and illustrated from the bank of Sabarmati estuary in the state of Gujarat of Peninsular India. The new species is closely allied with A. caracasana and A. pungens but differs in many attributes. The identity of the newly proposed species is confirmed by molecular analysis of three chloroplast DNA (cpDNA) regions viz., rbcL, psbA–trnH and trnL–trnF. The sequences showed that A. kanhae has an independent lineage to that of its sister clade.